Transforming Childhood Views: Phenomenology and Art in Research with Children - Reis, Brunara Batista; Alvim, Mônica Botelho (Revista de Psicología, 2021)
The article aims to discuss the research-intervention methodology of an interdisciplinary project based on phenomenology, gestalt therapy and art, presenting a profile of a research that problematized adult-centredness in understanding childhood in slums. Starting from Merleau-Ponty’s works on childhood, we understand the child as being-in-the-world, who perceives and dialogues bodily with another and experiences time, space and body in a unique way. Our methodology proposed an intervention-research focused on the child’s own experience, guided by the question “What is it like to be a child in Mangueira?”. By conducting workshops on artistic experimentation and group play, we were able to build a space for dialogue that would welcome the specificity of children’s modes of existence. The results are discussed based on vignettes cut from the log diaries, concluding that the ludic exercise motivates participation, transforming the child into a “researcher” and allows the researcher to rescue a “childhood body” and dialogue with the child open to the imagination and the way peculiar to experience space-time. The perception that adult-centredness was still de basis for the researchers’ gestures was an important element to reaffirm the need for attention to the problem and to reaffirm the adequacy of the methodological perspective of valuing the body and non-verbal expression.